2020
DOI: 10.1016/j.jmoldx.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hybrid Capture–Based Pan-Cancer Panel for Analysis of Treatment Stratifying Oncogenic Aberrations and Processes

Abstract: Stratification of patients for targeted and immune-based therapies requires extensive genomic profiling that enables sensitive detection of clinically relevant variants and interrogation of biomarkers, such as tumor mutational burden (TMB) and microsatellite instability (MSI). Detection of single and multiple nucleotide variants, copy number variants, MSI, and TMB was evaluated using a commercially available next-generation sequencing panel containing 523 cancer-related genes (1.94 megabases). Analysis of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Mutational signature analysis was performed as described previously. 2 The MPC described in the current paper is represented as UPN40 in Kroeze et al 2 In Figure 5 of the Kroeze et al study, the high contribution of signature 10a and 10b is demonstrated. 2…”
Section: Tumor Mutational Burden Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…Mutational signature analysis was performed as described previously. 2 The MPC described in the current paper is represented as UPN40 in Kroeze et al 2 In Figure 5 of the Kroeze et al study, the high contribution of signature 10a and 10b is demonstrated. 2…”
Section: Tumor Mutational Burden Analysismentioning
confidence: 80%
“… 24 Moreover, a major contribution of mutational signature 10a and 10b, associated with POLE mutations, indicates that somatic monoallelic mutation in the exonuclease domain of POLE is a main mutational process driving the tumorigenesis and responsible for high TMB in this MPC. 19 Germline mutations in POLE and POLD1 polymerases predispose to rare polymerase proofreading-associated polyposis, imposing increased risk to develop polyposis, early-onset colorectal cancer (CRC), and endometrial carcinomas (ECs). 22 Recently, a large family harboring a novel germline POLE variant was described to have multiple cancers including 3 early-onset PC cases, potentially indicating that PC belongs to the tumor spectrum of polymerase proofreading-associated polyposis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and RNA library preparations were performed separately using the hybrid capture-based TruSight Oncology (TSO) 500 DNA and RNA Library Preparation Kits, respectively (Illumina, San Diego, CA) according to the manufacturer's protocol essentially as described before. 15 The TSO500 DNA assay targets 523 cancer-related genes for assessment of single- and multiple-nucleotide variants, gene amplifications, tumor mutational burden (TMB), and microsatellite instability (MSI), whereas the RNA kit targets 55 genes for fusion gene analyses (Data Supplement). The use of unique molecular identifiers allows sensitive analysis of unique DNA molecules sequenced at every position.…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers such as tumor mutational burden (TMB) and microsatellite instability are useful for stratification of patients for targeted immuno-oncology therapies, which require extensive genomic profiling for sensitive detection of clinically relevant variants. Detection of single and multiple nucleotide variants ‒ CNVs, microsatellite instability, and TMB ‒ has been evaluated using a commercially available next generation sequencing (NGS) panel containing 523 cancer-related genes and can be applied for detection of multiple DNA-based biomarkers relevant for treatment selection [6].…”
Section: Role Of Biomarkers In Personalized Immuno-oncologymentioning
confidence: 99%